Determinants of the realisation of the right to adequate food of children (1 – 5 years old) and their primary caregivers living in rural and urban areas in one region of the Cacadu District in the Eastern Cape - Jenkings, Tamryn Caron (Stellenbosch : Stellenbosch University, 2016)
Thesis (MNutr)--Stellenbosch University, 2016.